Mosquito (Diptera: Culicidae) Fauna of Qom Province, Iran - A Saghafipour; MR Abai; B Farzinnia; R Nafar; H Ladonni; S Azari-Hamidian (Tehran University of Medical Sciences, 2012)
Background: There is very little information about the mosquito fauna of Qom Province, central Iran. By now only three species; Anopheles claviger, An. multicolor, and An. superpictus have been reported in the province. To study mosquito fauna and providing a primary checklist, an investigation was carried out on a collection of mosquitoes in this province. Methods: To study the mosquito (Diptera: Culicidae) fauna, larval collections were carried out from different habitats on 19 occasions using the standard dipping technique during spring and summer 2008 and 2009. Results: In total, 371 mosquito larvae were collected and morphologically identified including 14 species representing four genera: Anopheles claviger, An. marteri, An. turkhudi, An. superpictus, Culex arbieeni, Cx. hortensis, Cx. mimeticus, Cx. modestus, Cx. pipiens, Cx. territans, Cx. theileri, Culiseta longiareolata, Cs. subochrea, and Ochlerotatus caspius s.l. All species except for An. claviger and An. superpictus were collected for the first time in the province. All larvae were found in natural habitats. The association occasions and percentages of the mosquito larvae in Qom Province were discussed. Conclusion: There are some potential or proven vectors of different human and domesticated animal pathogens in Qom Province. The ecology of these species and the unstudied areas of Qom Province need to be investigated extensively.